Preparation of poly (bis[2-(methacryloyloxy)ethyl] phosphate) crosslinked polymer brushes on Poly(vinylidene fluoride) nanofibers - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2018)
In this study, a surface modification of poly(vinylidene fluoride) (PVDF) nanofibers by atom transfer radical polymerization (ATRP) was developed to form bis[2-(methacryloyloxy)ethyl] phosphate (BMEP) crosslinked polymer brushes grafted on nanofibers for application in rechargeable lithium batteries. BMEP was polymerized by using a grafting-from technique on the PVDF nanofiber surface by direct initiation. FT-IR (Fourier transform infrared) spectroscopy and SEM (scanning electron microscopy) confirmed the formation of BMEP polymer brushes. Morphological analysis showed that the diameter of the nanofibers was increased by surface grafting. Nevertheless, the characteristic nanofibrillar structure was not changed significantly by ATRP. The thermal properties of the nanofibers were investigated by TGA (thermogravimetric analysis). The results showed that the thermo-oxidative stability of the nanofibers increased with the BMEP content. The conductivities of Li-salts containing nanofibers were in the range 3.41 x 10(-3) S cm(-1) to 8.26 x 10(-4) S cm(-1).
Keywords: Surface-initiated ATRP; PVDF nanofiber; Ionic conductivity; Li-ion battery; LITHIUM-ION BATTERIES; OVERCHARGE PROTECTION; ELECTROLYTE MEMBRANE; CARBON NANOTUBES; FIBER MEMBRANES; PVDF MEMBRANE; ATRP; SURFACE; SAFETY; NANOCOMPOSITES